Measuring Social Health Following Pediatric Critical Illness: A Scoping Review and Conceptual Framework. (January 2023) - Daughtrey, Hannah; Slain, Katherine N.; Derrington, Sabrina; Evans, Idris V. R.; Goodman, Denise M.; Christie, LeeAnn M.; Li, Simon; Lin, John C.; Long, Debbie A.; Madden, Maureen A.; VandenBranden, Sara; Smith, McKenna; et al.
Objective: Social health is an important component of recovery following critical illness as modeled in the pediatric Post-Intensive Care Syndrome framework. We conducted a scoping review of studies measuring social outcomes (measurable components of social health) following pediatric critical illness and propose a conceptual framework of the social outcomes measured in these studies. Data sources: PubMed, EMBASE, PsycINFO, CINAHL, and the Cochrane Registry Study selection: We identified studies evaluating social outcomes in pediatric intensive care unit (PICU) survivors or their families from 1970–2017 as part of a broader scoping review of outcomes after pediatric critical illness. Data extraction: We identified articles by dual review and dual-extracted study characteristics, instruments, and instrument validation and administration information. For instruments used in studies evaluating a social outcome, we collected instrument content and described it using qualitative methods adapted to a scoping review. Data synthesis: Of 407 articles identified in the scoping review, 223 (55%) evaluated a social outcome. The majority were conducted in North America and the United Kingdom, with wide variation in methodology and population. Among these studies, 38 unique instruments were used to evaluate a social outcome. Specific social outcomes measured included individual (independence, attachment, empathy, social behaviors, social cognition, and social interest), environmental (community perceptions and environment), and network (activities and relationships) characteristics, together with school and family outcomes. While many instruments assessed more than one social outcome, no instrument evaluated all areas of social outcome. Conclusions: The full range of social outcomes reported following pediatric critical illness were not captured by any single instrument. The lack of a comprehensive instrument focused on social outcomes may contribute to under-appreciation of the importance of social outcomes and their under-representation in PICU outcomes research. A more comprehensive evaluation of social outcomes will improve understanding of overall recovery following pediatric critical illness.